Secure and efficient software implementation of QC-MDPC code-based cryptography - Guimarães, Antonio; Aranha, Diego F.; Borin, Edson (Anais Estendidos do Simpósio Brasileiro de Cibersegurança (SBSeg), 2020)
The emergence of quantum computers is pushing an unprecedented transition in the public key cryptography field. Algorithms in the current standard are vulnerable to attacks using quantum computers and need, therefore, to be replaced. Cryptosystems based on error-correcting codes are considered some of the most promising candidates to replace them for encryption schemes. Among the code families, QC-MDPC codes achieve the smallest key sizes while maintaining the desired security properties. Their performance, however, still needs to be greatly improved to reach a competitive level. In this work, we optimize the performance of QC-MDPC code-based cryptosystems through improvements concerning both their implementations and algorithms. We first present a new enhanced version of QcBits’ key encapsulation mechanism, which is a constant time implementation of the Niederreiter cryptosystem using QCMDPC codes. Comparing with the current state-of-the-art, the BIKE implementation, our code performs 1.9 times faster when decrypting messages. We then optimize the performance of QC-MDPC code-based cryptosystems through the insertion of a configurable failure rate in their arithmetic procedures. Using a failure rate negligible compared to the security level (2􀀀128), we achieve speedups of 1.6 to 2 times in some arithmetic algorithms. By inserting these algorithms in our enhanced version of QcBits, we were able to achieve a speedup of 1.9 on the key generation and up to 1.4 on the decryption time. Comparing with BIKE, our final version of QcBits performs the uniform decryption 2.7 times faster. Moreover, the techniques presented in this work can also be applied to BIKE, opening new possibilities for further improvements.